Deslocar os pensamentos: campesinato, transição agroecológica e relacionalidade na zona da mata de Minas Gerais - Faria, Mariana Vilhena de (2021)
The sharing of trajectories with peasants and with the Zona da Mata Agroecological Movement in Minas Gerais results in relational effects that are capable of modifying the ways in which we inhabit the world. Therefore, the question is: how do peasants contribute to knowledge building? The discussion is increasingly relevant in face of the environmental catastrophe of our time, in which the recognition of the dignity of every living being becomes key for us to live and die well. Dignity for all beings is still one of the main characteristic of the agroecological transition process. Through the construction of agroecological transition processes in a quilombola community, the organisation of a party in the countryside and a course of peasant therapies, I seek to narrate different moments of Agroecology production. Thus, I disseminate potentialities that manifest the presence of relationality as a central element of the peasant way of life. The relational condition of life is the main learning outcome and the most important result of the encounter between a researcher and Agroecology, unfolding in transformations in the most different aspects of our existence.